Are Evidence-based Practices Associated With Effective Prevention of Hospital-acquired Pressure Ulcers in US Academic Medical Centers?. Issue 5 (May 2016) - Padula, William V.; Gibbons, Robert D.; Valuck, Robert J.; Makic, Mary B.F.; Mishra, Manish K.; Pronovost, Peter J.; Meltzer, David O.
Abstract : Background: In 2008, the Centers for Medicare and Medicaid Services (CMS) established nonpayment policies resulting from costliness of hospital-acquired pressure ulcers (HAPUs) to hospitals. This prompted hospitals to adopt quality improvement (QI) interventions that increase use of evidence-based practices (EBPs) for HAPU prevention. Objective: To evaluate the longitudinal impact of CMS policy and QI adoption on HAPU rates. Materials and Methods: We characterized longitudinal adoption of 25 QI interventions that support EBPs through hospital leadership, staff, information technology, and performance and improvement. Quarterly counts of HAPU incidence and inpatient characteristics were collected from 55 University HealthSystem Consortium hospitals between 2007 and 2012. Mixed-effects regression models tested the longitudinal association of CMS policy, HAPU coding, and QI on HAPU rates. The models assumed level-2 random intercepts and random effects for CMS policy and EBP implementation to account for between-hospital variability in HAPU incidence. Results: Controlling for all 25 QI interventions, specific updates to EBPs for HAPU prevention had a significant, though modest reduction on HAPU rates (−1.86 cases/quarter; P =0.002) and the effect of CMS nonpayment policy on HAPU prevention was much greater (−11.32 cases/quarter; P <0.001). Conclusions: HAPU rates were significantly lower after changes in CMS reimbursement. Reductions are associated with hospital-wide implementation of EBPs for HAPU prevention. Given that administrative data were used, it remains unknown whether these improvements were due to changes in coding or improved quality of care.